EFFECT OF THE POSITIONING OF MULTIPLE CHARGING STATIONS FOR ELECTRIC VEHICLES ON GRID PERFORMANCE IN SAUDI ARABIA: THE CASE OF JEDDAH CITY - Mohammed Alqarni (JES: Journal of Engineering Sciences, 2022)
Electric vehicles (EV) have several advantages over traditional internal combustion vehicles, including lower local pollution, increased energy efficiency, and reduced reliance on oil. However, in many countries, such as Saudi Arabia (SA), considerable impediments to EV exist, including a lack of charging stations. What will happen as the future government strategy is to add a large number of charging stations in this country, and what effect will this have on the grid, particularly during the charging phase? The purpose of this research is to determine the power grid's capability in Saudi Arabia to house extra demand for EV charging. This research should aid in maintaining system stability and better planning for the future EV charging infrastructure. This paper aims to outline the effect of charging EVs on the grid and predict the possible number of charging stations that can be installed for a shopping mall parking space in Jeddah city. The data were collected from daily energy consumption and energy peak demand records from a shopping mall substation, and a total of eight EV charging scenarios were simulated. The load profile was analyzed for all scenarios, and as a result, 100% and 41% charging capacities are recommended for slow and fast charging methods, respectively.